Formation of Civil Activity at School children teenagers in the Process of Out-Of-Class Activity - Aigerim Baikulova4, Dinara Sadirbekova5., Babur Rakhimov1, Kundyz Uteyeva2, Ulzharkyn Аbdigapbarova3, (Opción, 2019)
The aim of the study is to investigate the formation of civilactivity at schoolchildren-teenagers in the process of out-of-classactivity via methods of mathematical statistics and graphicrepresentation of results. As a result, the school has to be the mostimportant institute of upbringing and education of younger generation,so exactly in these conditions, it has a special role in formation anddevelopment of the Kazakhstan patriotism. In conclusion, civil activityof schoolchildren is the integral component of process of all-rounddevelopment of the personality, result of socialization of the individualin the context of his national revival.